MEMBANGUN PARADIGMA BARU HUKUM PERUSAHAAN DAN ETIKA KEWIRAUSAHAAN - Wirazilmustaan Wirazilmustaan; Abdul Rasyid Saliman (PROGRESIF: Jurnal Hukum, 2017)
Curriculum of corporate law must be prepared to enter into the world of the industry with a very characteristic and distinctive, and the corporate law is not separated from the external business culture conditions develop. This means, the conditions of the external culture assumed already embedded in advance within the students, before they work in a company and then drift in the culture of the company. Because of its implication, build a new paradigm of curriculum into an absolute obligation to be met by faculty of law at this time. Construct curriculum based corporate law building the entrepreneurial spirit in faculty of law is the solution. The results showed that the revitalization of the new paradigm in developing corporate law should be immediately done. Where in the era of free market today many businessmen doing business without an understanding of corporate law and a strong corporate culture. The implications of this, the theories of corporate law, in the curriculum of lectures, also great for hindsight